Thin single-site catalytic polymer sheet
Patent Information
- Application Number
- JP2023565871
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-26
- Filing Date
- 2022-04-26
- Publication Date
- 2025-04-15
AI Technical Summary
Existing polyolefin sheets face issues with high wax content leading to processing problems, organoleptic concerns, and inadequate temperature resistance, which affect manufacturing efficiency and product quality.
Polymer sheets containing greater than 90% by weight of single-site catalyzed polyolefins with minimal wax and low molecular weight species, offering improved processability and enhanced temperature resistance.
The solution provides superior weight reduction, improved manufacturing efficiency, and enhanced temperature resistance, making them suitable for lightweight applications and food packaging without compromising on mechanical properties.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Application No. 63 / 179,873, filed April 26, 2021, which is incorporated by reference herein in its entirety for all purposes.
[0002] FIELD OF THEINVENTION The present invention generally relates to thin polymer sheets comprising single-site catalyzed polymers. Specifically, the present invention relates to polymer sheets comprising greater than 90% by weight of single-site catalyzed polyolefin (PO). The polymer sheets can have a thickness of at least 0.0254 centimeters (cm), preferably between 0.0254 cm and 0.1 cm. [Background technology]
[0003] Polyolefin films and sheets are used in a variety of consumer goods and commercial products. Traditionally, films are those with a thickness of less than 0.00254 cm, and sheets are those with a thickness of 0.00254 cm or more. Applications for thin sheets include container connectors for connecting multiple beverage containers, such as water, alcoholic beverage, or soft serve cans, which are well known. Such connectors are typically thin, flexible plastic sheets with a series of openings. Each opening is sized to receive a portion of a can. For example, a typical "six-pack" connector has six openings, each of which can engage the top ridge of a can. Similar connectors have been used to secure bottles and non-liquid containers. For example, U.S. Patent No. 5,399,333 to Bouge et al. describes a flexible beverage support sheet made of a multi-layer polymer, polyolefin foam sheet.
[0004] Other uses of polyolefin sheets include commercial products that include the sheets pressed together in combination with other materials (e.g., reinforcing materials). For example, U.S. Patent No. 5,399,433 to Yang et al. describes a polyolefin roofing membrane having a thickness of 35 mils to 90 mils (0.0889 cm to 0.2286 cm) that includes a reinforcing material between thermoplastic layers that include 50% to 90% by weight of a metallocene-catalyzed polyolefin (e.g., a copolymer of polyethylene and butene) and 10% to 50% by weight of an additive.
[0005] While polyolefin films and / or sheets are known, there is a need for polymer compositions that can be formed into sheets that provide desired properties and that allow for easy manufacturing of the polymer sheets without adversely affecting the desired properties. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Application Publication No. WO 2014 / 4204460 [Patent Document 2] U.S. Patent Application Publication No. 2004-157075 Summary of the Invention
[0007] A discovery has been made that provides a solution to at least some of the problems associated with polymer sheets. The discovery is based on a polymer sheet comprising greater than 90% by weight of single-site catalyzed polyolefin (PO). The discovery provides advantages in weight reduction due to superior physical properties of the polymer sheet, processability due to minimal or no presence of wax and / or low molecular weight species in the polymer sheet, and temperature resistance due to the high density of the polymer sheet. By way of example, the thin polymer sheet of the present invention can be used in light-weight applications over thick low density polyethylene. The thin polymer sheets of the present invention can be fully or partially substituted for polyethylene (LDPE) sheets. In another example, LDPE grades can have higher amounts of low molecular weight species and waxes than the thin polymer sheets of the present invention. Waxes can cause processing problems, such as increased die lip buildup, which impacts downtime on production costs. Waxy species are more mobile and therefore more likely to coat or be extracted from final articles made from LDPE. In addition, organoleptic problems with polymers can arise from a variety of sources, wax being one of them. As yet another example, the thin polymer sheets of the present invention can be temperature resistant (e.g., softening resistance), making them suitable for use in food packaging. Still further, the thin polymer sheets of the present invention can provide advantages over techniques previously provided through high melt flow rate (MFR) injection molding of LDPE and Linear LDPE (LLDPE) (e.g., injection molded lidstock, or overcap lid molding, etc.) because the sheets of the present invention are thermoformable.
[0008] In one aspect of the present invention, a polymer sheet is described. The polymer sheet of the present invention can comprise more than 90% by weight of single-site catalyzed polyolefin (PO) and have a thickness of at least 0.0254 cm. The PO material can comprise single-site catalyzed polyethylene (PE), single-site catalyzed polypropylene (PP), or copolymers thereof, or blends thereof. In some embodiments, the polymer sheet can comprise 90% by weight of single-site catalyzed PE and 10% or less of additional polymer. Non-limiting examples of additional polymers can include single-site catalyzed PP, single-site catalyzed copolymers, single-site catalyzed plastomers, elastomers, non-single-site catalyzed polyolefins, or blends thereof. Non-single-site catalyzed polyolefins can include low density polyolefin materials (e.g., LDPE or LDPP). In some embodiments, the polyolefin and / or polymer sheets of the present invention can have less than 30 wt% wax, less than 25 wt% wax, less than 20 wt% wax, less than 15 wt% wax, less than 10 wt% wax, less than 5 wt% wax, less than 4 wt% wax, less than 3 wt% wax, less than 2 wt% wax, less than 1 wt% wax, or no wax. The properties of the sheet can include thickness, density, tensile modulus, tensile strength, tensile toughness, impact energy, shrinkage %, load, or combinations thereof. The sheet thickness can be at least 0.0254 cm, 0.0254 cm to 0.1 cm, or 0.0254 cm to 0.0762 cm, or 0.0254 cm to 0.0508 cm. The density of the sheet can be at least 0.918 g / mL, or from 0.918 g / mL to 0.942 g / mL, or from 0.924 g / mL to 0.936 g / mL. The average tensile modulus of the polymer sheets of the invention can be at least 200 MPa, or from 300 MPa to 1300 MPa, or from 350 MPa to 800 MPa, or from 360 MPa. The sheets can have an average yield tensile strength that is higher than the average yield tensile strength of a low density polyethylene sheet (LDPE) at the same thickness.As an example, the polymer sheets of the present invention can have an average tensile strength at peak of at least 18.7 MPa, or at least 42 MPa. The average tensile toughness of the polymer sheets of the present invention can be at least 25 MPa, or from 50 MPa to 400 MPa, or from 55 MPa to 250 MPa. In some embodiments, the polymer sheets of the present invention can have a thickness of 0.0254 cm and an impact energy at 23° C. of greater than 1.5 kJ / m, or greater than 2.5 kJ / m, or at least 3.0 kJ / m, and / or an impact energy at −20° C. of greater than 2.5 kJ / m, or greater than 3.5 kJ / m, or at least 4.5 kJ / m. The polymer sheets of the present invention can have a shrinkage % less than or equal to that of an LDPE sheet of the same thickness under the same conditions, a higher energy to maximum load than an LDPE sheet of the same thickness under the same conditions, a higher heat distortion temperature (HDT) performance than an LDPE sheet of the same thickness under the same conditions, or any combination thereof. can be done.
[0009] In a further aspect of the present invention, an article of manufacture is described that includes the metallocene polymer sheet of the present invention. The article of manufacture may include a molded material, such as a multi-container ring holder, a four-pack ring, a six-pack ring, a twelve-pack ring, or an overcap lid.
[0010] In yet another aspect of the invention, a method of making a polymer sheet of the invention is described. A method can include subjecting a single-site catalyzed polymer having a melt flow index of 0.1 decigrams / minute to 10 decigrams / minute (dg / min), 0.25 dg / min to 7.5 dg / min, or 0.4 dg / min to 5.7 dg / min, and a density of at least 0.918 g / mL, 0.918 g / mL to 0.942 g / mL, or 0.924 g / mL to 0.936 g / mL, to conditions suitable for producing a sheet having a thickness of at least 0.0254 cm (e.g., 0.0254 cm to 0.1 cm, 0.0254 cm to 0.0762 cm, or 0.0254 cm to 0.0508 cm). The conditions can include extruding the single-site catalyzed polymer at a temperature of 175°C to 260°C, or 200°C to 235°C.
[0011] Other embodiments of the invention are discussed throughout this application. Any embodiment discussed with respect to one aspect of the invention applies to other aspects of the invention, and vice versa. Each embodiment described herein is construed as an embodiment of the invention applicable to other aspects of the invention. Any embodiment or aspect discussed herein is contemplated as being combinable with other embodiments or aspects discussed herein and / or implemented with respect to any method or composition of the invention, and vice versa. Furthermore, the compositions of the invention can be used to achieve the methods of the invention.
[0012] Listed below are definitions of various terms and phrases used throughout this specification.
[0013] Shrinkage can be calculated by first measuring the shrinkage length upon cooling in the direction along the flow (referred to as the longitudinal direction in the differential shrinkage measurement) and the shrinkage length occurring in the direction across the flow (referred to as the transverse direction in the differential shrinkage measurement). The shrinkage percentage is obtained by multiplying the difference between the shrinkage along the flow and the shrinkage across the flow by 100%. Shrinkage measurement is limited to measuring the change in the direction of resin flow and the change perpendicular to the direction of resin flow. Shrinkage can be measured using optical equipment as described in U.S. Pat. No. 7,445,827 or a computer numerically controlled (CNC) microscope. An example of a CNC microscope is the QV APEX 302 (Mitutoyo, USA). The polymer specimen can be a 60×60×2 mm polymer specimen formed from the polymer composition of the present disclosure according to ISO 294-3 Type D2. Optical measurement of specimen length is performed by placing the polymer specimen on a positioning table and placing the positioning table under a microscope camera, which is in communication with a microprocessor. The positions of both ends of the polymer specimen are recorded at the beginning and end of a period of time using specific markers on the microprocessor display screen. The length or width of the specimen is then estimated from the observed change in position over time. The processing parameters for shrinkage measurement are based on ISO 294-3 and ISO 294-1, with two notable differences: (1) for the same material, the fixation pressure can be selected from 20 MPa, 40 MPa, 60 MPa, or 80 MPa, and (2) the fixation time is kept to a minimum.
[0014] The phrases "melt flow rate" or "melt index (MFR or MI2)" refer to a measure of the ease with which a thermoplastic polymer or blend melt flows. "Melt flow rate" or MFR is used for polypropylene and "melt index" or MI2 is used for polyethylene and polyethylene rich blends. MFR values referred to herein are determined according to ASTM D 1238 at a temperature of 230°C using a ram weight of 2.16 kg. MFR measurements reported herein were made using a Tinuius-Olsen (USA) MP1200 melt flow indexer. MI2 values referred to herein are determined according to ASTM D 1238 at a temperature of 190°C using a ram weight of 2.16 kg. MI2 measurements reported herein were made using a Tinuius-Olsen MP993 melt flow indexer.
[0015] "Density" is defined as weight per volume. Density can be determined by ISO 1183.
[0016] The terms "about" or "approximately" are defined as close, as understood by one of ordinary skill in the art. In one non-limiting embodiment, these terms are defined as within 10%, preferably within 5%, more preferably within 1%, and most preferably within 0.5%.
[0017] The terms "wt. %, "vol. %, "or "mole %" refer to the weight percentage, volume percentage, or mole percentage, respectively, of a component based on the total weight, total volume of material, or total moles that include that component. In one non-limiting embodiment, 10 grams of a component in 100 grams of material is 10% by weight of a component.
[0018] The term "substantially" and variations thereof are defined to include within 10%, within 5%, within 1%, or within 0.5%.
[0019] The terms "inhibit" or "reduce" or "prevent" or "avoid" or variations of these terms, as used in the claims and / or specification, include any measurable reduction or complete inhibition that achieves the desired result.
[0020] The term "effective," as this term is used in the specification and / or claims, means adequate to accomplish a desired, expected, or intended result.
[0021] The use of the words "a" or "an" when used in the claims or in the specification with any of the terms "comprising," "including," "containing," or "having" can mean "one," but is not inconsistent with the meanings of "one or more," "at least one," and "one or more than one."
[0022] The terms "comprising" (and any form of comprising, e.g., "comprise" and "comprises"), "having" (and any form of having, e.g., "have" and "has"), "including" (and any form of including, e.g., "includes" and "include"), or "containing" (and any form of containing, e.g., "contains" and "contain") are inclusive or open-ended and do not exclude additional, unrecited elements or method steps.
[0023] The polymer sheets of the present invention can "comprise", "consist essentially of", or "consisting of" the specific components, elements, compositions, etc. disclosed throughout this specification. With respect to the transitional phrase "consist essentially of", in one non-limiting embodiment, a basic and novel feature of the polymer sheets is that they comprise greater than 90 wt. % single-site catalyst PO and have a thickness of at least 0.0254 cm.
[0024] Other objects, features, and advantages of the present invention will be apparent from the following drawings, detailed description, and examples. However, it should be understood that the drawings, detailed description, and examples, while showing specific embodiments of the present invention, are given by way of illustration only and are not meant to be limiting. Furthermore, it is contemplated that changes and modifications within the spirit and scope of the present invention will become apparent to those skilled in the art from this detailed description. In further embodiments, features from a specific embodiment can be combined with features from other embodiments. For example, features from one embodiment can be combined with features from any of the other embodiments. In further embodiments, further features can be added to the specific embodiments described herein. [Brief description of the drawings]
[0025] Advantages of the present invention may become apparent to those skilled in the art from the following detailed description and by reference to the accompanying drawings. [Figure 1] FIG. 1 shows a comparison of sheet thickness and % sheet shrinkage for a comparative LDPE sheet, a polymer sheet of the present invention, and an injection molded (IM) lid. [Diagram 2] FIG. 1 shows stiffness data for comparative LDPE sheets, inventive polymer sheets, and an IM lid. [Diagram 3] FIG. 1 shows the yield tensile strength of a comparative LDPE sheet, a polymer sheet of the present invention, and an IM lid. [Figure 4] FIG. 1 shows the maximum tensile strength of a comparative LDPE sheet, a polymer sheet of the present invention, and an IM lid. [Diagram 5] FIG. 1 shows the tensile toughness of a comparative LDPE sheet, an inventive polymer sheet, and an IM lid. [Figure 6] FIG. 1 shows the total impact energy of a comparative LDPE sheet, a polymer sheet of the present invention, and an IM lid. [Figure 7] FIG. 1 shows the total impact energy at maximum load for a comparative LDPE sheet, a polymer sheet of the present invention, and an IM lid. [Figure 8] FIG. 1 shows maximum load during impact for a comparative LDPE sheet, a polymer sheet of the present invention, and an IM lid. [Figure 9] FIG. 1 shows gel permeation data for comparative LDPE sheets, inventive polymer sheets, and a six-pack ring holder.
[0026] While the invention is susceptible to various modifications and alternative forms, specific embodiments of the invention are shown by way of example in the drawings. The drawings are not necessarily to scale. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] A discovery has been made that provides a solution to at least some of the problems associated with polyolefin-based sheets. The discovery is based on a polymer sheet that includes greater than 90% by weight of single-site catalyzed polyolefin, the sheet having a thickness of at least 0.0254 cm. The polymer sheet provides advantages in weight reduction, manufacturing of manufactured articles, and heat resistance.
[0028] These and other non-limiting aspects of the present invention are discussed in further detail in the following sections.
[0029] A. Polymer sheet The polymer sheet of the present invention can include more than 90 wt% single-site catalyzed polyolefin. In some embodiments, the polymer sheet can include at least one of 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, and 100 wt% single-site catalyzed PE, or an amount equal to or between any two of these, and an additional polymer, or an amount equal to or less than any one of 10, 9, 8, 7, 6, 5, 4, 3, 2, 1 wt% additional polymer. Non-limiting examples of additional polymers can include single-site catalyzed PP, single-site catalyzed copolymers, single-site catalyzed plastomers, elastomers, non-single-site catalyzed polyolefins, or blends thereof. Non-single-site catalyzed polyolefins can be low density polyolefin materials. Non-limiting examples of low density polyolefin materials include LDPE, LDPP, LLDPE, or any combination thereof. In some embodiments, the polyolefin and / or polymer sheets of the present invention can have wax at less than 30% by weight, or at amounts less than or equal to any one of 30, 29, 28, 27, 26, 25, 24, 23, 22, 21, 20, 19, 18, 17, 16, 15, 14, 13, 12, 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, or 0% by weight.
[0030] Properties of the polymer sheets of the present invention can include thickness, density, tensile modulus, tensile strength, tensile toughness, impact energy, shrinkage %, load, or combinations thereof. The sheet thickness can be from 0.0254 cm to 0.1 cm, or at least an amount equal to or between any two of 0.0254, 0.0260, 0.0270, 0.0280, 0.0290, 0.030, 0.035, 0.040, 0.045, 0.050, 0.055, 0.060, 0.065, 0.070, 0.075, 0.080, 0.085, 0.090, 0.095, and 0.1 cm. The density of the sheet can be at least 0.918 g / mL, or any one of 0.918, 0.920, 0.925, 0.930, 0.935, and 0.940 g / mL in at least some amount, or any one of these in an amount equal to, or any two of these in between. The average tensile modulus of the polymer sheet of the present invention can be at least 200 MPa, or any one of 200, 300, 400, 500, 600, 700, 800, 900, 1000, 1100, 1200, and 1300 MPa in at least some amount, or any one of these in an amount equal to, or any two of these in between. The average yield tensile strength is higher than that of a low density polyethylene sheet (LDPE) at the same thickness. By way of example, the polymer sheets of the present invention can have an average peak tensile strength that is at least 18.7 MPa, or at least one of 18.7 MPa, 19 MPa, 20 MPa, 25 MPa, 30 MPa, 35 MPa, 40 MPa, 45 MPa, 50 MPa, 55 MPa, 60 MPa, 65 MPa, 70 MPa, or greater, or an amount equal to any one of these, or an amount between any two of these.The average tensile toughness of the polymer sheets of the present invention can be at least 25 MPa, or at least an amount equal to or between any two of 25 MPa, 50 MPa, 100 MPa, 150 MPa, 200 MPa, 250 MPa, 300 MPa, 350 MPa, 400 MPa, and 450 MPa. In some embodiments, the polymer sheets have a thickness of 1) between 0.0254 cm and 0.1 cm, or between 0.0254 cm and 0.0762 cm, or between 0.0254 cm and 0.0508 cm; 2) a low density. 2) an average tensile modulus of at least 200 MPa, or 300 MPa to 1300 MPa, or 350 MPa to 800 MPa, or 360 MPa, 4) an average tensile strength at maximum of at least 18.7 MPa, or at least 42 MPa, 5) an average tensile toughness of at least 25 MPa, or 50 MPa to 400 MPa, or 55 MPa to 250 MPa, or any combination thereof. In some embodiments, the polymer sheet of the present invention can have a thickness of 0.0254 cm and an impact energy at 23° C. of greater than 1.5 kJ / m, or greater than 2.5 kJ / m, or at least 3.0 kJ / m, and / or an impact energy at −20° C. of greater than 2.5 kJ / m, or at least 4.5 kJ / m. The polymer sheets of the present invention may have a shrinkage % less than or equal to that of an LDPE sheet of the same thickness under the same conditions, a higher energy to maximum load than an LDPE sheet of the same thickness under the same conditions, a higher heat distortion temperature (HDT) performance than an LDPE sheet of the same thickness under the same conditions, or any combination thereof.
[0031] B. Polymer Sheet Manufacturing Method Preparation of the polymer sheet can be carried out using an extruder or other known sheet processing equipment. In certain aspects, the process can be carried out in an extruder by introducing additives or additional polymers to the single-site catalyzed polyolefin during processing. Non-limiting examples of extruders can include single screw extruders, counter-rotating and co-rotating twin screw extruders, planetary gear extruders, ring extruders, or co-kneaders. In some embodiments, the additional polymers or additives can be mixed with the resulting single-site catalyzed polyolefin prior to extrusion to produce a polymer blend. The single-site catalyzed polyolefin, and any optional components thereof, can be subjected to an elevated temperature for a sufficient length of time to incorporate the optional components with the single-site catalyzed polyolefin. The blending temperature can be above the softening point of the polymer. In certain aspects, a process can be carried out at a temperature of about 160°C to 280°C. Such "melt mixing" or "melt compounding" results in a homogeneous dispersion of the optional additives in the single-site catalyzed polyolefin polymer matrix.
[0032] In specific embodiments, polymer sheets of the present invention can be prepared by subjecting a single-site catalyzed polymer having a melt flow index of 0.1 decigrams / minute to 10 decigrams / minute (dg / min), 0.25 dg / min to 7.5 dg / min, or 0.4 dg / min to 5.7 dg / min, and a density of at least 0.918 g / mL, 0.918 g / mL to 0.942 g / mL, or 0.924 g / mL to 0.936 g / mL, to conditions suitable for producing a sheet having a thickness of at least 0.0254 cm. The conditions include extruding the single-site catalyzed polymer at a temperature at least one of, or equal to, any one of, or between any two of, 175, 180, 185, 190, 195, 200, 210, 215, 220, 225, 230, 235, 240, 245, 250, 255, and 260°C.
[0033] C. Single-site catalytic polymer The single-site catalyzed polymer can be any single-site catalyzed polyolefin having a melt flow index at least in an amount equal to, or between any two of, 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, and 10 dg / min, and a density at least in an amount equal to, or between any two of, 0.918, 0.920, 0.925, 0.930, 0.935, 0.940, 0.945 g / mL.
[0034] A polyolefin Examples of polyolefins include, but are not limited to, polypropylene and polyethylene. Polyethylene can include homopolymers of ethylene or copolymers of ethylene and at least one alpha-olefin (e.g., butene, hexene, octene, etc.). Examples of polyethylene include, but are not limited to, low density polyethylene (LDPE), linear low density polyethylene (LLDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), ethylene copolymers, or blends thereof. Polypropylene includes homopolymers of propylene, copolymers of propylene and other olefins, and terpolymers of propylene, ethylene, and dienes. Controlled rheology grade polypropylene (CRPP) is one that is further processed (e.g., through a degradation process) to produce polypropylene polymers with higher melt flow index (MFI), lower molecular weight, and / or narrower molecular weight distribution than the desired starting polypropylene. Reactor grades, also known as low dimensional polypropylene, can be used. Polyolefin homopolymers (e.g., PP homopolymer) can contain 0% to about 5% by weight (e.g., 0, 1, 2, 3, 4, 5% by weight, and any value or range thereof) of another alpha-olefin. Non-limiting examples of alpha-olefins include C2-C8 alpha-olefins, such as ethylene, 1-butene, and 1-hexene. Homopolymers can be prepared or obtained through commercial sources, such as TOTAL Petrochemicals, France and / or Total Petrochemicals USA, Inc. Non-limiting examples of homopolymers and copolymers include TOTAL Lumicene® brand.
[0035] b. Single-site catalyst A single-site catalyst is a catalyst that is a distinct chemical species, rather than a mixture of different species. Single-site catalysts can be supported or unsupported. Unsupported single-site catalysts are soluble in hydrocarbon solvents. Single-site catalysts can result in polyolefins with good, uniform comonomer incorporation with narrow molecular weight distribution (Mw / Mn<3). Single-site catalysts include late transition metal complexes and metallocenes. Late transition metals include groups 8-12 of the periodic table. Non-limiting examples of late transition metals include iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), ruthenium (Ru), rhodium (Rh), palladium (Pd), silver (Ag), cadmium (Cd), osmium (Os), iridium (Ir), platinum (Pt), and gold (Au). For example, late transition metal catalysts include nickel(II) and palladium(II) with nitrogen ligands.
[0036] Metallocenes can generally be characterized as coordination compounds incorporating one or more cyclopentadienyl (Cp) groups (which can be substituted or unsubstituted, and can be the same or different) coordinated to a transition metal through an n bond. The Cp groups can also have substitutions with linear, branched, or cyclic hydrocarbyl radicals, desirably cyclic hydrocarbyl radicals, to form other vicinal ring structures, such as indenyl, azulenyl, and fluorenyl groups. These additional ring structures can also be substituted or unsubstituted with hydrocarbyl radicals, desirably C1-C20 hydrocarbyl radicals. The metallocene compound can be combined with an activator and / or cocatalyst (as described in more detail below), or with the reaction product of an activator and / or cocatalyst, such as methylaluminoxane (MAO), and optionally with an alkylating / scavenging agent, such as trialkylaluminum compounds (TEAL, TMA, and / or TIBAL). Various metallocenes are known in the art and can be supported. Exemplary supports include any support, such as talc, inorganic oxides, Possible support materials include clays and clay minerals, ion-exchange layered compounds, diatomaceous earth, silicates, zeolites, or resin support materials such as polyolefins. Specific inorganic oxides include silica and alumina, used alone or in combination with other inorganic oxides such as magnesia, titania, zirconia, etc. Nonmetallocene transition metal compounds such as titanium tetrachloride are also incorporated into the supported catalyst components. The inorganic oxides used as supports are characterized by an average particle size of 30 microns to 600 microns, preferably 30 microns to 100 microns, a surface area of 50 square meters / gram to 1,000 square meters / gram, preferably 100 square meters / gram to 400 square meters / gram, and a pore volume in the range of 0.5 cc / g to 3.5 cc / g, preferably about 0.5 cc / g to 2 cc / g.
[0037] Any metallocene can be used in the practice of the present invention. As used herein, unless otherwise specified, "metallocene" includes a single metallocene composition or two or more metallocene compositions. Metallocenes are typically bulky ligand transition metal compounds, which are generally represented by the formula: [L] m M[A] nwhere L is a bulky ligand, A is a leaving group, M is a transition metal, and m and n are the total ligand valences corresponding to the transition metal valence. The ligands L and A can be bridged to each other, and when two ligands L and / or A are present, they can be bridged. The metallocene compound can be a full sandwich compound with two or more ligands L, where the ligand L can be a cyclopentadienyl ligand or a cyclopentadiene derived ligand, or a half sandwich compound with one ligand L, where the ligand L can be a cyclopentadienyl ligand or a cyclopentadiene derived ligand. The transition metal atom can be a Group 4, 5, or 6 transition metal and / or a metal of the lanthanide and actinide series of the periodic table. Non-limiting examples of metals include zirconium, titanium, and hafnium. Other ligands, such as leaving groups, can be attached to the transition metal. Examples of ligands include, but are not limited to, hydrocarbyl, hydrogen, or any other monovalent anionic ligand. For example, bridged metallocenes can be described by the general formula: RCpCp'MeQx. Me represents a transition metal element, Cp and Cp' each represent a cyclopentadienyl group, each of which can be the same or different and either substituted or unsubstituted, Q is an alkyl or other hydrocarbyl or halogen group, x is a number that can range from 1 to 3, and R is a structural bridge between the cyclopentadienyl rings. Metallocene catalysts and metallocene catalyst systems that produce isotactic polyolefins are disclosed in U.S. Pat. Nos. 4,794,096 and 4,975,403, which are incorporated herein by reference. These patents disclose chiral stereorigid metallocene catalysts that polymerize olefins to form isotactic polymers and are particularly useful for the polymerization of highly isotactic polypropylene.
[0038] Suitable metallocene catalysts are described, for example, in U.S. Pat. Nos. 4,530,914, 4,542,199, 4,769,910, 4,808,561, 4,871,705, 4,933,403, 4,937,299, 5,017,714, 5,026,798, 5,057,475, 5,120,867, 5,132,381, 5,155,180, 5,198,401, 5,278,119, 5,304,614, and 5,324,800. , No. 5,350,723, No. 5,391,790, No. 5,436,305, No. 5,510,502, No. 5,145 , No. 819, No. 5,243,001, No. 5,239,022, No. 5,329,033, No. 5,296,434, No. 5,296,434, No. No. 5,276,208, No. 5,672,668, No. 5,304,614, No. 5,374,752, No. 5,510,50 No. 2, No. 4,931,417, No. 5,532,396, No. 5,543,373, No. 6,100,214, No. 6,2 No. 28,795, No. 6,124,230, No. 6,114,479, No. 6,117,955, No. 6,087,291, No. 6,140,432, No. 6,245,706, No. 6,194,341 , No. 6,399,723, No. 6,380,334, No. 6,380,331, No. 6,380,330, No. 6,380,124, No. 6,380,123, No. 6,380,122, No. 6,380 ,121, EP No. 6,380,120, EP No. 6,376,627, EP No. 6,376,413, EP No. 6,376,412, EP No. 6,376,411, EP No. 6,376,410, EP No. 6,376,409, EP No. 6,376,408, EP No. 6,376,407, EP No. 5,635,437, EP No. 5,554,704, EP No. 6,218,558, EP No. 6,252,097, EP No. 6,255,515, and EP Publication No. 549 900, 576 970, and 611 773, as well as WO 97 / 32906, 98 / 014585, 98 / 22486, and 00 / 12565.
[0039] Metallocenes can be used in combination with some form of activator to create an active catalyst system. The term "activator" is defined herein as any compound or element, or combination of compounds or elements, capable of enhancing the ability of one or more metallocenes to polymerize olefins into polyolefins. Alklyalumoxanes, such as methylalumoxane (MAO), are commonly used as metallocene activators. Generally, alkylalumoxanes have about 5 to 40 repeat units. Alumoxane solutions, particularly methylalumoxane solutions, can be obtained from commercial vendors as solutions having various concentrations. There are various methods for preparing alumoxanes, examples of which include, but are not limited to, U.S. Pat. Nos. 4,665,208, 4,952,540, 5,091,352, 5,206,199, 5,204,419, 4,874,734, 4,924,018, 4,908,463, 4,968,827, 5,308,815, 5,329,032, 5,248,801, 5,235,081, 5,103,031, and EP-A-0 561 476, EP 0 279 586, EP-A-0 594 218, and WO 2003 / 023636. No. 94 / 10180, both of which are incorporated herein by reference in their entireties.
[0040] Ionizing activators can also be used to activate metallocenes. Such activators are neutral, ionic, or compounds that ionize the neutral metallocene compound, such as tri(n-butyl)ammonium tetrakis(pentafluorophenyl)borate. Such ionizing compounds can have an active proton, or some other cation, that is associated with the remaining ion of the ionizing compound, but is uncoordinated or loosely coordinated. Combinations of activators can also be used, such as alumoxanes combined with ionizing activators. See, for example, WO 94 / 07928.
[0041] Descriptions of ionic catalysts for coordination polymerization consisting of metallocene cations activated by non-coordinating anions appeared in early works in EP-A-0 277 003, EP-A-0 277 004, and US Pat. No. 5,198,401, and WO-A-92 / 00333, which are fully incorporated herein by reference. These teach a desirable preparation method in which metallocenes (bisCp and monoCp) are protonated with an anion precursor such that the alkyl / hydride group is abstracted from the transition metal to be both cationic and charge neutralized by a non-coordinating anion. Suitable ionic salts include aluminum salts with tetrakis-substituted borate or fluoroaryl components, such as phenyl, biphenyl, and naphthyl.
[0042] The term "noncoordinating anion" ("NCA") means an anion that is either not coordinated to the cation or that is only weakly coordinated to the cation so that it remains sufficiently susceptible to displacement by a neutral Lewis base. A "compatible" noncoordinating anion is one that does not decompose to neutrality when the initially formed complex decomposes. Furthermore, the anion does not undergo transfer of anionic substituents or fragments to the cation that would result in the formation of a neutral tetracoordinate metallocene compound and neutral by-products from the anion.
[0043] The use of ionizing ionic compounds that do not have an active proton but can generate both the active metallocene cation and the non-coordinating anion is also known. See, for example, EP-A-0426637 and EP-A-0573403, which are incorporated herein by reference in their entirety. A further method for preparing ionic catalysts uses ionizing anion precursors. These precursors are initially neutral Lewis acids, but upon ionizing reaction with the metallocene compound, they form cations and anions, for example, tris(pentafluorophenyl)borane is used. See, for example, EP-A-0520732, which is incorporated herein by reference in its entirety. Ionic catalysts for addition polymerization can also be prepared by oxidation of the metal center of a transition metal compound with an anion precursor that has a metallic oxidizing group in combination with the anion group. See, for example, EP-A-0495375, which is incorporated herein by reference in its entirety.
[0044] Where the metal ligands bear halogen moieties which are not capable of ionizing abstraction under standard conditions (e.g. bis-cyclopentadienyl zirconium dichloride), these can be converted by known alkylation reactions with organometallic compounds, e.g. lithium hydride or alkyl lithium or aluminum hydrides or alkyl aluminums, alkyl alumoxanes, Grignard reagents, etc. For in situ processes see EP-A-0 500 944 and EP-A1-0 570 982, which describe the reaction of alkyl aluminum compounds with dihalo substituted metallocene compounds before or with the addition of an activating anionic compound.
[0045] The preferred method of supporting ionic catalysts including metallocene cations and NCAs is described in U.S. Patent Nos. 5,643,847, 6,228,795, and 6,143,686, each of which is fully incorporated herein by reference. When using a support composition, these NCA supporting methods can include the use of a neutral anion precursor that is a Lewis acid strong enough to react with the hydroxyl reactive groups present on the silica surface so that the Lewis acid becomes covalently bonded. Furthermore, when the activator for the metallocene supported catalyst composition is an NCA, the NCA is preferably added to the support composition first, followed by the metallocene catalyst. When the activator is an MAO, the MAO and metallocene catalyst are preferably dissolved together in a solution. The support is then contacted with the MAO / metallocene catalyst solution. Other methods and addition orders will be apparent to those skilled in the art.
[0046] c. Single-site polyolefin manufacturing Single-site polyolefins can be formed by placing one or more olefin monomers (e.g., ethylene, propylene) in a suitable reaction vessel, alone or with other monomers, in the presence of a single-site catalyst and under suitable reaction conditions for their polymerization. Any equipment and process suitable for polymerizing olefins into polymers can be used. For example, such processes can include solution phase processes, gas phase processes, slurry phase processes, bulk phase processes, high pressure processes, or combinations thereof. Such processes are described in U.S. Patents 5,525,678; 6,420,580; 6,380,328; 6,359,072; 6,340,411; and 6,420,580. Nos. 6,586, 6,340,730, 6,339,134, 6,300,436, 6,274,684, 6,271,323, 6,248,845, 6,245,868, 6,245,705, 6,242,545, 6,211,105, 6,207,606, 6,180,735, and 6,147,173, each of which is fully incorporated herein by reference.
[0047] Single-site polyolefins can be formed by a gas phase polymerization process. One example of a gas phase polymerization process is a continuous cycle system, in which a cycling gas stream (otherwise known as a recycle stream or fluidized medium) is heated in a reactor by heat of polymerization. Heat is removed from the cycling gas stream in another part of the cycle by a cooling system external to the reactor. The cycling gas stream containing one or more monomers can be continuously cycled through a fluidized bed under reactive conditions in the presence of a catalyst. The cycling gas stream is generally withdrawn from the fluidized bed and recycled back to the reactor. At the same time, single-site polyolefin polymer can be withdrawn from the reactor and fresh monomer can be added to replace the polymerized monomer. The reactor pressure in the gas phase process can vary from 100 psig to 500 psig, or from 200 psig to 400 psig, or from 250 psig to 350 psig. The reactor temperature in the gas phase process can be from 30°C to 120°C, or from 60°C to 115°C, or from 70°C to 110°C, or from 70°C to 95°C. Exemplary, but not limiting, polymer processes are described in U.S. Pat. Nos. 4,543,399, 4,588,790, 5,028,670, 5,317,036, 5,352,749, 5,405,922, 5,436,304, 5,456,471, 5,462,999, 5,616,661, 5,627,242, 5,665,818, 5,677,375, and 5,668,228, which are incorporated herein by reference in their entirety.
[0048] D. Manufactured products The polymer sheets of the present invention can be stored for a period of time, used as is, or can be used immediately in a forming process that can include thermoforming or molding. Formed articles can include beverage rings, lids such as six-pack ring holders, overcap lids, and the like. EXAMPLES
[0049] The present invention will be described in more detail by way of specific examples. The following examples are provided for illustrative purposes only and are not intended to limit the present invention in any manner. Those skilled in the art will easily understand that various non-critical parameters can be changed or modified to obtain essentially the same results.
[0050] Example 1 (Single-site catalyzed polyolefin extruded sheet, comparison LDPE, and comparison injection molded (IM) lid) Five different materials were tested for their potential use in various sheet applications. The first material was a LDPE reference material made using a non-single-site catalyst (LDPE#1, Westlake EF403 (fractionated melt low density compound, melt index 0.8 g / 10 min and density 0.924 g / cm3) from Westlake Chemical (USA). 3 ) and the other four were metallocene medium density polyethylene materials (designated mPE#1-#4, available from TOTAL, USA). Sheets were produced on a Davis Standard Sheet Line using a 1.5 inch diameter main extruder with a vertical 3-roll stack. Each of the five materials was used to produce sheets at 10, 15, 2 Extruded sheets were produced in a variety of thicknesses, including 0, 10, 20, 30, and 30 mils (i.e., 0.010", 0.015", 0.020", and 0.030"). Tables 1 and 2 summarize the properties of the LDPE sheets produced with a non-single-site catalyst, the polymer sheets of various thicknesses produced with a single-site catalyst, and a commercially available injection molded lid made from LLDPE. The lids were 4.6 inches (11.68 cm) in diameter, weighed 9.6 g, and were 23.7 mils (0.061 cm) thick.
[0051] Sheet shrinkage decreased with increasing sheet thickness (Figure 1). LDPE showed similar shrinkage performance to mPE#1 and mPE#2 sheets, which have the most similar density. mPE#3 showed much less shrinkage than LDPE, and mPE#4 behaved very differently from the other samples (shrinking similarly in both M and T directions). The injection molded lid was expected to have better shrinkage properties than the mPE sheets due to the lack of high molecular weight species. Higher molecular weight species tend to maintain orientation if it occurs during processing. With fewer high molecular weight chains, relaxation of the melt orientation in all directions can occur quickly before the melt completely solidifies. That is, the cast sheets can be expected to shrink more due to the higher molecular weight. In fact, the advantage shown by the injection molded lid was surprisingly small. The cast sheets had similar shrinkage properties to the injection molded lids (see Figure 1). The machine direction shrinkage was between that of mPE#3 and mPE#1. The transverse shrinkage was slightly higher than mPE#3. This data predicts that single-site catalyzed polymer sheets can be used successfully in any melt phase thermoforming part, melt billet phase forming, as well as very shallow draw thermoforming (e.g., drape forming) such as found in lidstock.
[0052] The mPE sheets showed superior tensile performance in stiffness (Figure 2), strength (Figure 3), and toughness (Figure 4) compared to the LDPE sheets. Overall, the sheet thickness was not very sensitive to the normalized tensile properties, indicating that these tensile properties can be treated more or less directly as material properties (not affected by application). The data determined that the IM lid was softer, which was expected due to its lower density. Thus, the single-site polymer sheets of the present invention can be used for weight reduction because sheets made from single-site polymers can be downgauged while still meeting or exceeding current market expectations in lidding.
[0053] Yield strength has some correlation with stiffness and is an important attribute in identifying when forces will permanently deform an article. For closures, yield stress can be important in high speed filling operations as well as to the consumer (e.g., if the closure is difficult to peel off, it may permanently deform). Injection molded closures performed similarly to mPE#1 and mPE#2 and yielded more easily than mPE#3 or mPE#4 (see Figure 3). Lids made with either mPE#3 or mPE#4 could be lighter by 15 mils (0.0381 cm) and still match or exceed the yield strength of the injection molded closures.
[0054] In addition to the point at which a tensile specimen may yield, the maximum stress achieved may also be important in some applications, since this includes the hardening phenomenon achieved before tensile failure. In this case, all of the single-site catalyzed polymers of the present invention showed very good maximum strength (see FIG. 4). This indicates that further weight reductions may be achievable for applications that are designed around maximum strength instead of yield strength.
[0055] The tensile data is also used to illustrate the ability of each sheet to absorb energy under relatively slow loading (as opposed to the impact tests discussed below). The stress-strain data is integrated to The total energy was calculated by multiplying by the initial volume of the test area. The machine direction data is shown in Figure 5. However, the transverse data was very similar. As expected, the thinner the sheet, the more tensile energy it was able to absorb. For the most part, the data followed the trends exhibited by the stiffness and strength. The main exceptions were mPE#4 and the IM lid. For mPE#4, the ultimate strength was significantly lower (indicating less orientation-driven stiffening), which contributed to the relatively low tensile energy. The IM lid showed an extremely low elongation to break, significantly lowering the calculated tensile energy. Overall, this finding provided an indication of how much energy it may take to slowly tear or puncture a sheet.
[0056] Impact drop test is a particularly important property in packaging. Inventory loss, such as due to package damage, is referred to as shrinkage in the retail industry. Broken food containers are problematic at the consumer level because damage can be a point of entry for pathogens, can cause food leakage, and can be a source of dissatisfaction among other things. The impact performance of most mPE sheets (except mPE#4, which has a high MFI) showed excellent impact performance at both room temperature and -20°C (see Figure 5). This increase in performance was proportional to the sheet thickness after applying a transfer factor of +0.42 ft-lb for the room temperature results and 1.10 ft-lb for the -20°C results. The data determined that the sheet thickness of mPE#2 was reduced by 38% without any loss in tensile or impact performance. These properties could be even higher in some cases. Both room temperature and -20°C impact tests on the IM lid demonstrated that the single-site catalyzed polymer sheet option was superior. Samples mPE#1, mPE#2, and mPE#3 all showed better impact performance at 10 mils (0.0245 cm), which is only 42% of the thickness of the IM lid. Even mPE#4, with a 5.7 MI2 and 0.933 g / cc density, gave the same impact performance at only 15 mils (0.0381 cm). Thus, the use of single-site catalyzed polymer sheets allows for substantial weight reduction without sacrificing drop impact performance. [Table 1] [Table 2-1] [Table 2-2]
[0057] Example 2 (Extruded sheets of single-site catalyzed polyolefins, comparative LDPE, and comparative thick Spackling) The polymer sheet samples mPE#1-mPE#4 of the present invention, the comparative LDPE, and the commercially available six-pack ring material were analyzed and compared. Table 3 summarizes the DSC and density of the samples. The six-pack ring showed a density of 0.930 g / cc, which was higher than that of the comparative LDPE. This indicates that the six-pack ring was a higher density product. The enthalpy is significantly higher. The density of mPE#3 was similar to the six-pack ring. The data identified that the polymer sheet of the present invention is suitable for six-pack ring manufacturing, as the density and DSC are comparable to the commercial products. [Table 3]
[0058] The rheological test results for the six samples are summarized in Table 4. Density was included for reference of the whole molecular architecture. [Table 4]
[0059] Dynamic temperature frequency sweeps were performed to further understand the rheological comparison. The comparisons are summarized in Table 5. These defined the Carreau-Yasuda parameters to further optimize the molecular architecture. It was possible to match the zero shear viscosity with the mPE samples with fractional melt index. The shorter relaxation times of the polymer sheets of the present invention indicated that they had lower melt strength, but in cast sheets this can be compensated for in processing. This can have some benefit in reducing the amount of rheological stress going from frozen to melt, since it is quenched in the cast sheet roll stack. [Table 5]
[0060] Another processing criterion is wax concentration. Higher wax concentrations (lower molecular weight species) can lead to a variety of processing difficulties. Smokiness, die lip adhesion, and roll stock adhesion are three potential problems. Some processing techniques require special "grease traps" to collect such low molecular weight material to prevent equipment contamination and downtime.
[0061] Wax testing identified advantages of the inventive polymer sheets. All four inventive polymer sheets tested had significantly less wax than six-pack ring and LDPE (see Table 6). The lack of wax provides advantages of improved processing, improved physical properties, and reduced weight. [Table 6]
[0062] The GPC data was consistent with the wax results. The data is summarized in Table 7. The average molecular weights showed a narrower molecular weight range for the single-site catalyzed polyolefins. Although this left behind fewer high molecular weight species, it removed many of the waxy species that did not contribute significantly to the physical properties. [Table 7]
[0063] The molecular weight differences are illustrated by the overlay of the GPC slice data (see Figure 9). The six-pack holder had a very broad, nearly bimodal distribution shape. The LDPE comparative example had a narrower molecular weight distribution. These differences may be based on reactor technology, as it is known that tubular versus autoclave technology can result in different molecular weight architectures.
[0064] In summary, the mPE polymer sheets of the present invention exhibited: (1) less variability in molecular weight, with polydispersity ranging from 2.6 to 2.8 for mPE versus 3.7 for LDPE, (2) less wax (1% to 20%) than LDPE (55%), (3) less ash content (0.02% to 0.04%) than LDPE (0.27%), (4) higher melting point, which increases with increasing density but decreases with increasing MFI, (5) lower rheological activation energy (27 kJ / mol to 31 kJ / mol) than LDPE (49 kJ / mol), which is a measure of the temperature sensitivity of the melting point properties, (6) higher storage and loss moduli in dynamic mechanical analysis by torsion, and (7) higher estimated HDT performance. For example, for a threshold strain of 0.20%, the estimated HDT for mPE was 147°C to 167°C, compared to 133°C for LDPE. Also, the use of the polymer sheets of the present invention provides an option to use LDPE in six-pack ring manufacturing. As an example, the polymer sheets of the present invention had a lower content of low molecular weight species, which is consistent with the lower wax results.
[0065] Although the embodiments of the present application and their advantages have been described in detail, it should be understood that various changes, substitutions, and alterations can be made herein without departing from the spirit and scope of the embodiments as defined by the appended claims. Moreover, the scope of the present application is not intended to be limited to the particular embodiments of the processes, machines, manufacture, compositions, means, methods, and steps described herein. As one skilled in the art will readily recognize from the above disclosure, there are currently existing or later developed processes, machines, manufacture, compositions, means, methods, or steps that perform substantially the same function or achieve substantially the same results as the corresponding embodiments described herein. Accordingly, the appended claims are intended to include within their scope such processes, machines, manufacture, compositions, means, methods, or steps.
Claims
1. 1. A polymer sheet comprising greater than 90% by weight of a single-site catalyzed polyolefin (PO), said sheet having a thickness of at least 0.0254 cm.
2. 10. The polymer sheet of claim 1, wherein the PO material comprises single-site catalyzed polyethylene (PE), single-site catalyzed polypropylene (PP), or copolymers thereof, or blends thereof.
3. 3. The polymer sheet of claim 2, wherein the polymer sheet comprises 90% by weight of single-site catalyzed PE and up to 10% of additional polymer.
4. 4. The polymer sheet of claim 3, wherein the additional polymer is a single-site catalyzed PP, a single-site catalyzed copolymer, a single-site catalyzed plastomer, an elastomer, a non-single-site catalyzed polyolefin, or a blend thereof.
5. 5. The polymer sheet of claim 4, wherein the non-single-site catalyzed polyolefin is a low density polyolefin material.
6. 6. The polymer sheet of claim 5, wherein the low density polyolefin material is LDPE or LDPP.
7. 10. The polymeric sheet of claim 1, wherein the sheet thickness is from 0.0254 cm to 0.1 cm, or from 0.0254 cm to 0.0762 cm, or from 0.0254 cm to 0.0508 cm.
8. 10. The polymer sheet of claim 1, wherein the sheet has a density of at least 0.918 g / mL, or from 0.918 g / mL to 0.942 g / mL, or from 0.924 g / mL to 0.936 g / mL.
9. 2. The polymer sheet of claim 1, having an average tensile modulus of at least 200 MPa, or from 300 MPa to 1300 MPa, or from 350 MPa to 800 MPa, or 360 MPa.
10. 10. The polymer sheet of claim 1, having an average yield tensile strength greater than the average yield tensile strength of a low density polyethylene sheet (LDPE) of the same thickness.
11. 11. The polymer sheet of claim 10, having an average maximum tensile strength of at least 18.7 MPa, or at least 42 MPa.
12. 10. The polymer sheet of claim 1, having an average tensile toughness of at least 25 MPa, or from 50 MPa to 400 MPa, or from 55 MPa to 250 MPa.
13. 10. The polymer sheet of claim 1, wherein the polymer sheet has a thickness of 0.0254 cm and an impact energy at 23° C. of greater than 1.5 kJ / m, or greater than 2.5 kJ / m, or at least 3.0 kJ / m.
14. 10. The polymer sheet of claim 1, wherein the polymer sheet has a thickness of 0.0254 cm and an impact energy at -20°C of 2.5 kJ / m, or greater than 3.5 kJ / m, or at least 4.5 kJ / m.
15. 10. The polymer sheet of claim 1 having a shrinkage % less than or equal to the shrinkage % of an LDPE sheet of the same thickness under the same conditions.
16. 10. The polymer sheet of claim 1 having a higher energy to maximum load than a LDPE sheet of the same thickness under the same conditions.
17. 10. The polymer sheet of claim 1, wherein the polyolefin comprises less than 30% by weight of wax.
18. 20. The polymer sheet of claim 17, wherein the polyolefin comprises less than 25% by weight wax, less than 15% by weight wax, less than 10% by weight wax, less than 5% by weight wax, or no wax.
19. 10. The polymer sheet of claim 1, having a heat distortion temperature (HDT) performance higher than the HDT of a LDPE sheet of the same thickness under the same conditions.
20. An article of manufacture comprising the metallocene polymer sheet of any one of claims 1 to 19.
21. 21. The article of manufacture of claim 20, wherein the article of manufacture is a molded material.
22. 22. The article of manufacture of claim 21, wherein the molded material is a multi-container ring holder.
23. 23. The article of manufacture of claim 22, wherein the molded material is an overcap lid.
24. 1. A method of making a polymer sheet comprising subjecting a single-site catalyzed polyolefin polymer having a melt flow index of from 0.1 decigrams / minute to 10 decigrams / minute (dg / min), or from 0.25 dg / min to 7.5 dg / min, or from 0.4 dg / min to 5.7 dg / min, and a density of at least 0.918 g / mL, or from 0.918 g / mL to 0.942 g / mL, or from 0.924 g / mL to 0.936 g / mL, to conditions suitable for producing a sheet having a thickness of at least 0.0254 cm.
25. 25. The method of claim 24, wherein the conditions include extruding the single-site catalyzed polymer at a temperature of from 175°C to 260°C or from 200°C to 235°C.
26. The method of any one of claims 24 to 25, wherein the thickness is between 0.0254 cm and 0.1 cm, between 0.0254 cm and 0.0762 cm, or between 0.0254 cm and 0.0508 cm.